Modelling the mediating role of place attachment and tourist satisfaction on destination loyalty in the Malaysian tourism industry - Muhamad Nasyat Muhamad Nasir
The tourism industry in Malaysia is an important sector that contributes to the national economy. This study was carried out on Langkawi Island, the first and only Global Geopark in Malaysia recognized by UNESCO, which is facing a sluggish and unstable growth rate pattern of international tourist arrivals. Therefore, the arrivals of international tourists to Langkawi Island can be improved by studying the island's destination loyalty. Previous studies suggested that several constructs such as destination attractiveness, service quality, place attachment and tourist satisfaction were found to be the predicting factors of destination loyalty. The objectives of this study are, first, to detennine the effects of destination attractiveness and service quality on place attachment, tourist satisfaction and destination loyalty; second to determine the effects of place attachment and tourist satisfaction on destination loyalty; third to determine the mediating effects of place attachment and tourist satisfaction on the relationship between de tination attractiveness and destination loyalty; and fourth to determine the mediating effects of place attachment and tourist satisfaction on the r lationship between service quality and destination loyalty. The study employed a cross-sectional research design. A total respondent of 365 tourists from France, Germany and Netherlands visiting Langkawi Island were selected from a sampling frame using simple random sampling technique in SPSS. Self-administered questionnaires were distributed to the respondents at the Langkawi International Airport after the pre-test and pilot test were conducted. Confirmatory Factor Analysis was performed to validate the measurement model of the study using several tests such as unidimensionality, validity and reliability test. The study applied the Structural Equation Modelling to test the hypotheses. The findings of the study supported all the hypotheses involves the relationship between independent variable, mediator and dependent variable. Moreover, they revealed that place attachment and tourist satisfaction fully mediate the relationship between destination attractiveness and destination loyalty. Meanwhile, place attachment and tourist satisfaction partially mediate the relationship between service quality and destination loyalty. The findings of this study contributed to the theoretical implication which suggested a new structural model that examined the relationships among destination attractiveness, service quality, place attachment, tourist satisfaction and destination loyalty. The study suggested several practical contributions to the tourism management of Langkawi Island in order to enhance international tourists' loyalty, especially tourists from France, Germany and Netherlands, to the island. Future research should include other variables such as quality of life, tourist experience and trust which probably could explain more about the variance in destination loyalty.